2017
DOI: 10.1186/s40635-017-0144-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an ADVanced Organ Support (ADVOS) system in a two-hit porcine model of liver failure plus endotoxemia

Abstract: BackgroundNovel extracorporeal procedures are constantly being developed and evaluated for use in patients with sepsis. Preclinical evaluation of such procedures usually requires testing in large animal models. In the present work, the safety and efficacy of a recently developed ADVanced Organ Support (ADVOS) system in a newly developed large animal two-hit model of liver failure combined with endotoxemia were tested.MethodsAfter establishing the model in more than 50 animals, a randomized study was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Preclinical studies demonstrated high detoxification rates for protein-bound and water-soluble toxins. Removal of relevant amounts of CO 2 at blood flow rates typical for renal replacement therapies was shown in vitro [21][22][23]. A clinical case series using a prototype of the system demonstrated the ability to remove water-soluble and albumin-bound substances [24].…”
Section: ]mentioning
confidence: 99%
“…Preclinical studies demonstrated high detoxification rates for protein-bound and water-soluble toxins. Removal of relevant amounts of CO 2 at blood flow rates typical for renal replacement therapies was shown in vitro [21][22][23]. A clinical case series using a prototype of the system demonstrated the ability to remove water-soluble and albumin-bound substances [24].…”
Section: ]mentioning
confidence: 99%
“…The free portion of toxins is then removed by a filtration process. The acidified and the alkalinized albumin dialysates finally join each other so that a physiological pH is generated before passage in the dialysate compartment of the haemodialyzers [29].…”
Section: Discussionmentioning
confidence: 99%
“…A modified device called advanced organ support (ADVOS) was first presented in 2013, which included a dialysate circuit containing standard dialysate with a 2-4% albumin concentration, an extracorporeal blood circuit, and a third and last circuit where the albumin dialysate was separated into two parts. Each part would undergo a PH and temperature change before reaching the cation and anion filters, resulting in dialysates that have albumin that is free of toxins [49,50]. This is accomplished by adding and removing acid or base.…”
Section: Other Devicesmentioning
confidence: 99%